2008
DOI: 10.1182/blood-2008-04-152967
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the myeloid progenitor compartment in Down syndrome fetal liver precede acquisition of GATA1 mutations

Abstract: Down syndrome (DS) children have a high frequency of acute megakaryoblastic leukemia (AMKL) in early childhood. At least 2 in utero genetic events are required, although not sufficient, for DS-AMKL: trisomy 21 (T21) and N-terminal-truncating GATA1 mutations. To investigate the role of T21 in DS-AMKL, we compared second trimester hemopoiesis in DS without GATA1 mutations to gestation-matched normal controls. In all DS fetal livers (FLs), but not marrows, megakaryocyteerythroid progenitor frequency was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
125
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(142 citation statements)
references
References 23 publications
15
125
1
1
Order By: Relevance
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…3,28 TL likely arises from fetal liver hematopoietic progenitor cells after the acquisition of GATA1 mutations in the context of cellular trisomy 21. This hypothesis is supported by the detection of GATA1 mutations in DS fetal liver cells, 29 expanded numbers of megakaryocyte-erythroid progenitor cells during DS fetal hematopoiesis, 30 and the increased proliferative capacity conferred to murine fetal liver GATA1 mutations of all engrafted samples were shown to be concordant with those present in the primary human cell samples. c Primary sample; codon 13 of N-RAS (NC_000001.10; nucleotide 115258813-5).…”
Section: Discussionsupporting
confidence: 63%
“…However, none of these mouse strains develop TL and AMKL, indicating that additional genetic abnormalities are required to cause leukemia. In humans as well, trisomy 21 itself has been shown to disturb fetal liver, but not bone marrow, hematopoiesis, enhance production of megakaryocyte/erythroid progenitors (MEPs), which may be susceptible to acquisition of other genetic abnormalities, and predispose these cells to DS-related leukemias (Chou et al, 2008;De Vita et al, 2008;Tunstall-Pedoe et al, 2008). These data support the model that the genes on chromosome 21 play essential roles in the development of these disorders and trisomy 21 is the first step of myeloid leukemogenesis in DS.…”
Section: Multistep Model Of Myeloid Leukemogenesis In Children With Dssupporting
confidence: 72%